Analisis Yuridis terhadap Tindak Pidana Kekerasan (Pengeroyokan) yang Menyebabkan Kematian - Anak Agung Istri Nadia Maheswari Devi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widiantara (Jurnal Preferensi Hukum, 2025)
Crimes of violence (brawling) always exist in society, and tend to increase and develop in society in line with the times. The crime of violence (beating) is a criminal offense that relates to moral issues and feelings. Based on this, How is the legal regulation of the crime of violence (beating)? And how are the criminal sanctions against the perpetrators of beatings that cause death? This research uses normative legal research. Legal arrangements against criminal acts of violence (beating) which is a criminal act as regulated in Article 358 of the Criminal Code which provides a maximum imprisonment of two years and eight months and a maximum of two years. Criminal sanctions against perpetrators of beatings that cause death are regulated in Article 170 paragraph (1) of the Criminal Code which will be sentenced to a maximum imprisonment of 5 years and 6 months, as well as other sanctions regarding beatings are also regulated in Article 358 of the Criminal Code.